English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

12 - 1 x 6 ÷ 3 x 2 + 1

Thanks.

2007-06-17 12:57:00 · 9 answers · asked by jay 1 in Science & Mathematics Mathematics

9 answers

12-4+1=9

2007-06-17 12:59:47 · answer #1 · answered by UNIQUE 3 · 2 0

12

2007-06-17 13:43:40 · answer #2 · answered by Anonymous · 0 0

The order of operations is:
parentheses or grouping symbols
exponents
multiplication and division (left to right)
addition and subtraction (left to right)

12 - 1 x 6 / 3 x 2 + 1

=12 - 6 / 3 x 2 + 1

= 12 - 2 x 2 + 1

= 12 - 4 + 1

= 8 + 1

= 9

2007-06-17 13:06:49 · answer #3 · answered by mathjoe 3 · 1 0

12 - 1 x 6 ÷ 3 x 2 + 1
= 12 - 6 / 3 * 2 + 1
= 12 - 2*2 + 1
= 12 - 4 + 1
= 9.

2007-06-17 13:00:13 · answer #4 · answered by Anonymous · 2 1

12

2007-06-17 13:04:21 · answer #5 · answered by Anonymous · 1 2

WOO! :) pass Cinny! vast Bang infant - Stone Temple Pilots. Tangerine - Led Zeppelin. Bunker Hill - purple warm Chili Peppers. Subway To Venus - purple warm Chili Peppers. bitter woman - Stone Temple Pilots. end! - Jane's habit. indignant Chair - Alice In Chains. seek And destroy - Iggy Pop And The Stooges. do not end Me Now - Queen. Ourobourous - The Mars Volta. Cicatriz E.S.P. - The Mars Volta. proprietor Of A Lonely coronary heart - sure. Bonus; April 19.

2016-11-25 19:20:02 · answer #6 · answered by Anonymous · 0 0

12 - (1 x 6) ÷ 3 x( 2 + 1) =
(12-6) ÷ (3x3) =
6 ÷ 9 = 2/3
****************

2007-06-17 13:05:13 · answer #7 · answered by CHARTIGER 2 · 0 2

first multiply and divide left to right, getting

12 - 4 + 1

then add and subtract left to right, getting

9

2007-06-17 13:00:27 · answer #8 · answered by Philo 7 · 2 1

9...

2007-06-17 13:06:35 · answer #9 · answered by ShaH 6 · 0 0

fedest.com, questions and answers